2001
DOI: 10.1093/pasj/53.6.1211
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric Abundances of Volatile and Refractory Elements in Planet-Harboring Stars

Abstract: By using the high-dispersion spectra of 14 bright planet-harboring stars (along with 4 reference stars) observed with the new coudé echelle spectrograph at Okayama Astrophysical Observatory, we investigated the abundances of volatile elements (C, N, O, S, Zn; low condensation temperature T c ) in order to examine whether these show any significant difference compared to the abundances of other refractory elements (Si, Ti, V, Fe, Co, Ni; high T c ) which are known to be generally overabundant in those stars wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 21 publications
3
60
2
Order By: Relevance
“…Nevertheless, Smith et al (2001) found, using a collection of abundance data from the literature, that about six stars exhibit positive slopes. Other authors (Gonzalez 2006a,b;Sadakane et al 2002;Takeda et al 2001) found no dependence of the abundances on T C .…”
Section: The Link Between Migration and Stellar Abundancesmentioning
confidence: 85%
“…Nevertheless, Smith et al (2001) found, using a collection of abundance data from the literature, that about six stars exhibit positive slopes. Other authors (Gonzalez 2006a,b;Sadakane et al 2002;Takeda et al 2001) found no dependence of the abundances on T C .…”
Section: The Link Between Migration and Stellar Abundancesmentioning
confidence: 85%
“…Previous studies (e.g., Smith et al 2001;Takeda et al 2001;Santos et al 2004;Ecuvillon et al 2006;Gonzalez & Laws 2007) have been cautious about reaching strong conclusions based on abundance trends with T C because of the still relatively large systematic errors associated with their analyses in comparison with the small size of the effect. To detect this trend, a precision of 0.03 dex or better is required.…”
Section: Planetary Signatures In the Abundance Trends?mentioning
confidence: 99%
“…It may be worthwhile, from another point of view, to check the consistency of this treatment on nearby solar-type stars, which have been recently analyzed by Takeda et al (2001) to study the abundance characteristics of planet-harboring stars. Figure 12 shows the comparison of the non-LTE abundance of O  7771-5 triplet (with the NLTE correction obtained by using the formula described in this study) with the LTE abundance of O  6158.2 (a) and [O ] 6300.3 (b), which were derived from either equivalent-widths or spectrum-synthesis technique (with the same line data as given in Table 1) as described in Takeda et al (2001).…”
Section: Appendix A: On the Effect And Treatment Of H I Collisionmentioning
confidence: 99%
“…Figure 12 shows the comparison of the non-LTE abundance of O  7771-5 triplet (with the NLTE correction obtained by using the formula described in this study) with the LTE abundance of O  6158.2 (a) and [O ] 6300.3 (b), which were derived from either equivalent-widths or spectrum-synthesis technique (with the same line data as given in Table 1) as described in Takeda et al (2001). Note that LTE can be safely applied to these latter two lines (cf.…”
Section: Appendix A: On the Effect And Treatment Of H I Collisionmentioning
confidence: 99%